Forecasting the price of wheat and other commodities - Pfaffenzeller, Stephan (2002)
The long term behaviour of primary product prices has been a central issue underlying projections of commodity price series. Against the background of the Prebisch Singer Hypothesis, the presence, magnitude and direction of a secular trend in commodity price series have themselves become the subject of a long standing debate.